Math, asked by Devansy3845, 1 year ago

Value of -(-(-2/3))=x then value of x

Answers

Answered by BlackpinkfanShivuhi
0

-(-(- 2/3)) = x

- + - = +

+(- 2/3)) = x

+ + - = -

- 2/3 = x

-2 / x = 3

x = 3 + 2

x = 5

Answered by sheeb12ansari
0

Given: -(-(-2/3))=x

We have to find the value ofx.

By using the Bodmas rule, we are solving the above equation.

As we know that the Bodmas rule is used to remember the order of operations to be followed while solving expressions in mathematics.

Where,

\begin{array}{l}\mathrm{B}=\text{brackets}\\\mathrm{O}=\text { order of powers or rules } \\\mathrm{D}=\text { division } \\\mathrm{M}=\text { multiplication } \\\mathrm{A}=\text { addition } \\\mathrm{S}=\text { subtraction }\end{array}

We are solving in the following way:

We have,

-(-(-2/3))=x

=>(+(-\frac{2}{3} ))=x\\\\=>x=-\frac{2}{3}

Hence, the value ofx is-\frac{2}{3}.

Similar questions